STUDY ON IMPLEMENTATION OF GMP AND SSOP OF YELLOWFIN SOLE (Limanda aspera) SANDWICH PRODUCTS AT PT BUMI MENARA INTERNUSA SURABAYA - Panjaitan, Pola S.T.; Rizkiah, Riza; Arifianto, Sakti; Soeharso, Agusta Putri Balqis Linda; Sulistiyo, Budi; Ningsih, Trisna (Aurelia Journal, 2025)
Fish is a food source rich in nutritional value, yet highly perishable and susceptible to rapid quality deterioration. The aim of this research was to evaluate the implementation of GMP and SSOP in the processing of sandwich yellowfin sole products, and the basic feasibility of the fish processing unit at PT Bumi Menara Internusa Surabaya. This study used qualitative descriptive method through a gap analysis of the application of GMP, SSOP, and basic feasibility. The results showed that, according to the Ministry of Maritime Affairs and Fisheries Regulation Number 17 of 2019, the implementation of GMP and SSOP has been carried out effectively and met the required standards for basic feasibility, with no critical, serious, minor, or major findings, earning the Excellent (A) rating. The production process of frozen sandwich yellowfin sole at PT Bumi Menara Internusa Surabaya includes raw material receiving, thawing, weighing 1, washing 1, skinning, filleting, V cutting, trimming, bone and parasite control, washing 2, joining married portion, layering, IQF freezing, sorting and sizing, weighing 2, glazing, metal detecting, polybag packaging, MC packaging, weighing 3, frozen storage, and stuffing, all of which have effectively implemented the cold chain system, as demonstrated by the temperature observation table for the products, room, and water (good cold chain). The yield obtained after the skinning process of yellowfin sole was 90%.